Documentation relating to the entries on Éamonn Duggan's career in biographical dictionaries, - Adam and Charles Black (Firm) (1936)
Documentation issued by the publishers of 'Who's Who' and the 'Catholic Who's Who' concerning their biographical entries on Eamonn Duggan for their forthcoming editions. Both communications contain drafts of their entries on Duggan's career.